2013
DOI: 10.3122/jabfm.2013.05.120247
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Failure and Costs in Patients With Methicillin-Resistant Staphylococcus aureus (MRSA) Skin and Soft Tissue Infections: A South Texas Ambulatory Research Network (STARNet) Study

Abstract: Objective To measure the incidence of treatment failure and associated costs in patients with methicillin-resistant Staphylococcus aureus (MRSA) skin and soft tissue infections (SSTIs). Methods This was a prospective, observational study in 13 primary care clinics. Primary care providers collected clinical data, wound swabs, and 90-day follow-up information. Patients were considered to have “moderate or complicated” SSTIs if they had a lesion ≥ 5 cm in diameter or diabetes mellitus. Treatment failure was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 24 publications
0
46
1
Order By: Relevance
“…In this study, our failure rate was 24%, which is higher than that in previously published studies with a range of 10% to 21% (3)(4)(5)(6)(7). This may be due to the increased number of overweight and obese patients compared to prior studies.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In this study, our failure rate was 24%, which is higher than that in previously published studies with a range of 10% to 21% (3)(4)(5)(6)(7). This may be due to the increased number of overweight and obese patients compared to prior studies.…”
Section: Discussioncontrasting
confidence: 53%
“…In the literature, the overall treatment failure rate of oral antibiotics ranges from 10% to 21% (3)(4)(5)(6)(7). One study found that the mean additional cost associated with antibiotic failure was $1,934 per patient (5).…”
mentioning
confidence: 99%
“…Skin infections are a common clinical problem resulting in substantial clinical morbidity, hospitalization, and cost (1,2,24). In this study, postdischarge adherence to antibiotic therapy for S. aureus skin infection was low (57%) and associated with poor clinical outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Although these are often mild infections, they can lead to severe invasive diseases such as bacteremia, endocarditis, osteomyelitis, and sepsis. S. aureus infections can also be difficult to completely eradicate even when the infecting isolate is susceptible to antibiotics (3,4). This is further complicated by the emergence and spread of methicillin-resistant S. aureus (MRSA) along with an increasing incidence of resistance to macrolides, aminoglycosides, and fluoroquinolones (5) and more recently linezolid (LZD) (6,7).…”
mentioning
confidence: 99%